Concordance between the Different Cardiovascular Risk Scores in People with Rheumatoid Arthritis and Psoriasis Arthritis - Cristina Gonzalez-Martin; Silvia Grande Morais; Sonia Pertega-Diaz; Teresa Seoane-Pillado; Vanesa Balboa-Barreiro; Raquel Veiga-Seijo (Cardiology Research and Practice)
Aim. To determine the cardiovascular risk and the concordance between the different scores in people with rheumatoid arthritis (RA) and psoriatic arthritis (PsA). Methods. Observational descriptive study of prevalence. Performed in the Rheumatology Service and the Clinical Epidemiology and Biostatistics Unit of the University Hospital Complex of A Coruña (Spain). Patients diagnosed with RA or PsA, older than 18 years of age were included. Measurements: sociodemographic, anthropometric variables of the disease, comorbidity, cardiovascular risk, and therapeutic management. Results. 151 subjects (75 RA and 76 PsA) were studied. The average age was 57.9 ± 12.2 years, 61.6% being women. The average of the Charlson index was 2.8 ± 1.5. 43% were overweight. 46.5% were classified as cardiovascular risk, and the average percentage was 33.3% by Framingham. The best agreement has been between Framingham and Dorica (k = 0.709; p<0.001), classifying more than 80% of the cases in the same risk categories. Conclusions. The most prevalent risk factors were overweight and obesity, followed by smoking and hypertension. The prevalence of patients with moderate/high cardiovascular risk varies according to the score used, the levels of concordance being the scores of Framingham and Dorica.